Systematic Literature Review: Pemanfaatan Aplikasi Photomath Sebagai Media Belajar Matematika - Sri Damayani; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to identify the use of the photomath application as a mathematics learning medium. This research method uses the SLR (Systematic Literature Review) method. This systematic review identified 6 articles through the Google Scholar database published in 2019-2024. Data collection used the PRISMA procedure. The results of this research show that the photomath application is very helpful in learning activities, especially in mathematics lessons. The photomath application apart from making it easier for students in the learning process, the photomath application also helps teachers in explaining the material. In this way, using the Photomath application will certainly get good feedback for educators or students who use it well.